2001
DOI: 10.1139/g00-099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of resistance factors toPhytophthora palmivorain cocoa

Abstract: Phytophthora palmivora causes pod rot, a serious disease on cocoa widespread throughout the producing regions. In order to ascertain the genetic determination of cocoa resistance to P. palmivora, a study was carried out on two progenies derived from crosses between a heterozygous, moderately resistant Forastero clone, T60/887, and two closely related and highly susceptible Forastero clones, one completely homozygous, IFC2, and one partially heterozygous, IFC5. The cumulative size of both progenies was 112 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
3
25
0
1
Order By: Relevance
“…Indeed, UPA 402 is an Upper-Amazon Forastero clone obtained from a sibmating involving two Forastero genotypes collected in Peru and may be highly homozygous for this linkage group. A similar situation, where a small number of markers were also assigned to LG8, was observed in other maps established by Clement et al (2003) and Flament et al (2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed, UPA 402 is an Upper-Amazon Forastero clone obtained from a sibmating involving two Forastero genotypes collected in Peru and may be highly homozygous for this linkage group. A similar situation, where a small number of markers were also assigned to LG8, was observed in other maps established by Clement et al (2003) and Flament et al (2001).…”
Section: Discussionsupporting
confidence: 80%
“…These maps were based on codominant markers such as restriction fragment length polymorphisms (RFLPs), isoenzymes and a small number of simple sequence repeats (SSRs) and, in some of the maps, associated with dominant amplified fragment length polymorphisms (AFLP) and random amplified polymorphic DNA (RAPD) markers. They have been used to locate quantitative trait loci (QTLs) affecting traits of interest, such as disease resistance and yield factors (Crouzillat et al 2000;Flament et al 2001;Clement et al 2003;Queiroz et al 2003;Risterucci et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several regions of the genome involved in yield components and Phytophthora spp. resistance were identified (Crouzillat et al 2000;Flament et al 2001;Lanaud et al 2002;ClØment et al 2003aClØment et al , 2003bRisterucci et al 2003) and confirmed the polygenic nature of this quantitative resistance in cocoa. A region of chromosome 6 appears particularly interesting and gave QTL for yield components and resistance to Phytophthora.…”
Section: Introductionmentioning
confidence: 82%
“…The genetic reference map of Theobroma cacao L. has been developed using the progeny UPA402 × UF676 (Lanaud et al 1995;Pugh et al 2004). And, QTLs for resistance to Phytophthora also, for agronomic and quality traits were identified (Lanaud et al 1999;Flament et al 2001;Risterucci et al 2003;Clément et al 2003a,b).…”
Section: Africamentioning
confidence: 99%